An update on the development of antiviral against Mayaro virus: from molecules to potential viral targets - Paschoalino, Marina; Marinho, Mikaela dos Santos; Santos, Igor Andrade; Grosche, Victória Riquena [UNESP]; Martins, Daniel Oliveira Silva [UNESP]; Rosa, Rafael Borges; Jardim, Ana Carolina Gomes [UNESP] (Springer Nature, 2023)
Mayaro virus (MAYV), first isolated in 1954 in Trinidad and Tobago islands, is the causative agent of Mayaro fever, a disease characterized by fever, rashes, headaches, myalgia, and arthralgia. The infection can progress to a chronic condition in over 50% of cases, with persistent arthralgia, which can lead to the disability of the infected individuals. MAYV is mainly transmitted through the bite of the female Haemagogus spp. mosquito genus. However, studies demonstrate that Aedes aegypti is also a vector, contributing to the spread of MAYV beyond endemic areas, given the vast geographical distribution of the mosquito. Besides, the similarity of antigenic sites with other Alphavirus complicates the diagnoses of MAYV, contributing to underreporting of the disease. Nowadays, there are no antiviral drugs available to treat infected patients, being the clinical management based on analgesics and non-steroidal anti-inflammatory drugs. In this context, this review aims to summarize compounds that have demonstrated antiviral activity against MAYV in vitro, as well as discuss the potentiality of viral proteins as targets for the development of antiviral drugs against MAYV. Finally, through rationalization of the data presented herein, we wish to encourage further research encompassing these compounds as potential anti-MAYV drug candidates.
Keywords: Antiviral; Mayaro fever; Mayaro virus; Natural and synthetic compounds; Viral targets